THE INFLUENCE OF TAX SANCTIONS ON INDIVIDUAL TAXPAYER COMPLIANCE IN KIHIYANG VILLAGE - Muhammad Syeh Dinar (Journal of Taxation Analysis and Review, 2021)
Indonesia is a developing country that has a wealth of abundant resources. In addition, Indonesia has the potential to be called a developed country. However, currently Indonesia is still not able to maximize its potential and resources for the prosperity of its population. There are many aspects that make Indonesia worse off when compared to other developing countries. The most important aspect that makes our economy slump is income from the tax sector. The purpose of this study was to determine how much influence tax sanctions have on individual taxpayer compliance in Kihiyang Village. The population used in this study is an individual taxpayer in the Kihiyang village, Binong district, Subang district, West Java. Data were collected by distributing questionnaires. The analysis technique uses simple linear regression analysis. The results showed that the coefficient of determination R2 was 31%, which means the remaining 69% was explained by other variables. The results of this study conclude that Tax Sanctions have a positive and significant effect on mandatory compliance of individuals in Kihiyang Village.